Predictors of changes in physical activity and sedentary behavior during the COVID-19 pandemic in a Turkish migrant cohort in Germany - Krist, Lilian; Dornquast, Christina; Reinhold, Thomas; Icke, Katja; Danquah, Ina; Willich, Stefan N.; Becher, Heiko; Keil, Thomas (International journal of environmental research and public health, 2021)
The new coronavirus (COVID-19) pandemic and the resulting response measures have led to severe limitations of people’s exercise possibilities with diminished physical activity (PA) and increased sedentary behavior (SB). Since for migrant groups in Germany, no data is available, this study aimed to investigate factors associated with changes in PA and SB in a sample of Turkish descent. Participants of a prospective cohort study (adults of Turkish descent, living in Berlin, Germany) completed a questionnaire regarding COVID-19 related topics including PA and SB since February 2020. Changes in PA and SB were described, and sociodemographic, migrant-related, and health-related predictors of PA decrease and SB increase were determined using multivariable regression analyses. Of 106 participants, 69% reported a decline of PA, 36% reported an increase in SB. PA decrease and SB increase seemed to be associated with inactivity before the pandemic as well as with the female sex. SB increase appeared to be additionally associated with educational level and BMI. The COVID-19 pandemic and the response measures had persistent detrimental effects on this migrant population. Since sufficient PA before the pandemic had the strongest association with maintaining PA and SB during the crisis, the German government and public health professionals should prioritize PA promotion in this vulnerable group.